ON THE CHECK BOARD OF DISPUTES (ON THE PROBLEM OF SWEAR WORDS WORLDWIDE) - Ткачівська , М. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of swear words in different linguistic cultures, considering the process of their usage from the earliest times and up to nowadays. The article highlights main characteristic features of invectives in different countries of the world, and analyses them. The main invective strategies are outlined.